Presentation - Humanística, Universitas (Editorial Pontificia Universidad Javeriana, 2015)
The dossier number 81 of the journal Universitas Humanistica aimed at collecting critical theoretical reflections and case studies that inquire into the role of communication processes in the generation of social changes. These transformations were understood in a broad sense, including all the possible nuances between mobilizations and interventions tending towards problematizing and destabilizing status-quo, as well as initiatives that transgress the social order with both reactionary and oppresive objectives.